Monitoring Urban Expansion and Its Impact on Agricultural and Forest Lands in Al-Qarabulli Municipality (Journal of Libya for geographical studies, 2026)
This study examines urban expansion in Al-Qarabulli Municipality and its impact on agricultural and forest lands using remote sensing techniques and Geographic Information Systems (GIS). The study area has been experiencing rapid urban growth in the absence of land-use planning based on approved planning standards. The main objectives of this research are to monitor urban expansion in Al-Qarabulli, assess its impacts on agricultural and forest lands, analyze the factors driving this expansion, and highlight the importance of remote sensing and GIS in studying urban growth, its spatial extent, stages, and directional trends. The results reveal a rapid increase in urban areas within the municipality, where the proportion of built-up land rose from 4.2% in 2010 to 31.7% of the total municipal area in 2025. Consequently, agricultural land decreased from 299 km² and forest land from 78.7 km² in 2000 to 138 km² and 43.5 km², respectively, in 2025. During the same period, built-up areas expanded from 10.4 km² in 2000 to 128.7 km² in 2025. These changes indicate substantial encroachment on agricultural and forest lands between 2000 and 2025, amounting to approximately 161 km² of agricultural land (about 54%) and around 35 km² of forest land (68.6%). This represents a significant reduction in vegetation cover within the municipality. At the same time, urban areas increased by approximately 118 km², reflecting a growth rate of about 113% over the same period.
Keywords: Urban expansion; Geographic Information Systems (GIS); remote sensing